TRADISI MAKAN BAJAMBA DI NAGARI SIALANG, KECAMATAN KAPUR IX, KABUPATEN LIMA PULUH KOTA - Rido Jamallius; Abrar Abrar (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2026)
Makan bajamba is one of the cultural heritages of the Minangkabau community that embodies the values of togetherness, equality, mutual cooperation, and religiosity. However, modernization and changing patterns of social interaction have affected the transmission of these customary values to younger generations. This study aims to examine the implementation of the makan bajamba tradition in Nagari Sialang, Kapur IX District, Lima Puluh Kota Regency, and to explore the social, religious, and cultural values embedded in the tradition as well as their relevance to contemporary society using a qualitative ethnographic approach. Data were collected through participant observation, in-depth interviews with traditional leaders, religious leaders, village government officials, and local community members, as well as documentation studies. The data were analyzed through data reduction, data display, conclusion drawing, and triangulation to ensure the credibility of the findings. The results indicate that makan bajamba is not merely a communal dining practice but also serves as a medium for transmitting customary values and Islamic teachings, strengthening social solidarity, fostering egalitarian relationships, reinforcing kinship ties, and preserving Minangkabau cultural identity across generations. The study concludes that the makan bajamba tradition remains sustainable and relevant despite ongoing social changes because the community has successfully preserved its core values while adapting its practices to contemporary conditions. Consequently, the tradition continues to contribute to the preservation of local culture and the strengthening of social cohesion within Minangkabau society.